Excessive or reduced rest-day sleep compensation linked to depression in Chinese adults - Song, Yanliqing; Wang, Long; Liu, Yue (Frontiers in Psychiatry, 2025)
BackgroundThis study aims to evaluate the impact of Rest Day Catch-up Sleep (RDCS) patterns on depression among Chinese adults during the pandemic and to explore the relationship between different levels of compensation and the likelihood of depression.MethodsThis study included 3,981 participants, who were divided into five groups based on changes in rest day sleep duration: no change in sleep duration (RDCS = 0 h), reduced sleep duration (RDCS < 0), moderate catch-up sleep (1 h < RDCS < 2 h), and long catch-up sleep (RDCS ≥ 2 h). A multivariable logistic regression model was used to analyze the relationship between RDCS and depression. Stratified logistic regression and interaction effect analyses were conducted to explore demographic differences in the association between RDCS and depression.ResultsIn the fully adjusted model, participants with reduced sleep duration had an odds ratio (OR) of 2.12 (95%CI [1.31 – 3.46]) for depression, while those with long catch-up sleep had an OR of 1.60 (95%CI [1.29 – 1.98]). Stratified logistic regression and interaction effect analyses indicated that the association between RDCS < 0 h and depression was more significant among individuals with a Body Mass Index (BMI) < 25 kg/m², while the association between RDCS ≥ 2 h and depression was more significant among individuals with a general self-rated health status.ConclusionThe results of this study indicate that both reduced sleep duration and excessive catch-up sleep during the pandemic are associated with an increased likelihood of depression. These findings highlight the importance of maintaining stable sleep patterns during special periods and provide scientific evidence for the development of targeted public health interventions.